PENERJEMAHAN METAFORA NOVEL LELAKI HARIMAU KE DALAM L’HOMME TIGRE - Putri Astari, Gita (JURNAL ILMU BUDAYA, 2019)
This research aims to analyze the translation of metaphors in the novel Lelaki Harimau byEka Kurniawan in French. The theory used in this research is the theory of metaphor and thetheory of metaphor translation. Metaphor is a comparative language style that is divided intofour types: anthropomorphic metaphor, animal metaphor, concrete to abstract metaphor andsynthesis metaphor. The theory of metaphor translation is used to analyze the translationstrategies. This research is qualitative with the approach of translation theory. Based on theresults of the study, it is known that although some translations of metaphors have weakenedthe degree of emotional expressions and some metaphorical expressions cannot be literallyaccepted in the target language, in general, the translation Lelaki Harimau to L’homme Tigrecan be judged as good.